The Relationship between Body Mass Index in Pregnancy and Adverse Maternal, Perinatal, and Neonatal Outcomes in Rural India and Pakistan - Short, Vanessa L.; Geller, Stacie E.; Moore, Janet L.; McClure, Elizabeth M.; Goudar, Shivaprasad S.; Dhaded, Sangappa M.; Kodkany, Bhalachandra S.; Saleem, Sarah; Naqvi, Farnaz; Pasha, Omrana; Goldenberg, Robert L.; Patel, Archana B.; Hibberd, Patricia L.; Garces, Ana L.; Koso-Thomas, Marion; Miodovnik, Menachem; Wallace, Dennis D.; Derman, Richard J. (American Journal of Perinatology, 2018)
Objective The objective of this study was to describe the relationship between early pregnancy body mass index (BMI) and maternal, perinatal, and neonatal outcomes in rural India and Pakistan.Study Design In a prospective, population-based pregnancy registry implemented in communities in Thatta, Pakistan and Nagpur and Belagavi, India, we obtained women's BMI prior to 12 weeks' gestation (categorized as underweight, normal, overweight, and obese following World Health Organization criteria). Outcomes were assessed 42 days postpartum.Results The proportion of women with an adverse maternal outcome increased with increasing maternal BMI. Less than one-third of nonoverweight/nonobese women, 47.2% of overweight women, and 56.0% of obese women experienced an adverse maternal outcome. After controlling for site, maternal age and parity, risks of hypertensive disease/severe preeclampsia/eclampsia, cesarean/assisted delivery, and antibiotic use were higher among women with higher BMIs. Overweight women also had significantly higher risk of perinatal and early neonatal mortality compared with underweight/normal BMI women. Overweight women had a significantly higher perinatal mortality rate.Conclusion High BMI in early pregnancy was associated with increased risk of adverse maternal, perinatal, and neonatal outcomes in rural India and Pakistan. These findings present an opportunity to inform efforts for women to optimize weight prior to conception to improve pregnancy outcomes.
Keywords: body mass index; Asia; perinatal mortality; global health